Níquel em solo e plantas de milho cultivadas em área tratada com lodo de esgoto durante 15 anos consecutivos - Alves, Suelen Cristina Nunes [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The waste solid urban production waste is growing because the steady population has increase. One of these residues is the sewage sludge (SS). This residue has been shown to be a good alternative for fertilization of agricultural soils, because it is a material rich in nutrients for plants and potential source of organic matter. Sewage sludge must be managed with caution because it contains metals, pathogens and toxic organic compounds in their constitution, to aim the environmentally sustainable use. The objective of this study was to quantify the Ni element and the pseudo-total content available in organic matter fractions (humic acid, fulvic acid). In addition, we evaluated the soil Ni adsorption and evaluated the absorbed by corn plants. The experiment was conducted in field conditions at UNESP - Jaboticabal experimental area. The design was a complete randomized block with four treatments and five replications. The treatments were, T0 - no sludge, T5 - 5 t.ha-1 of SS, T10 - 10 t.ha-1 of SS and T20 - 20 t.ha-1 of SS. The used sludge had its origin from the sewage treatment station, ETE-SABESP located in Monte Alto, SP. In the depth from 0.05 to 0.10 m, the pseudo-total content of Ni was increased from 75.9 to 107.3 mg.kg-1 depending of sludge doses, while the available Ni content has not been changed. In organic matter fractions, the surface layer was the one that showed the highest levels of Ni, for both humic acid and fulvic acid, with significant at 0.05 - 0.10 m. The results of adsorption performed was adjusted to Freundlich’s isotherm with coefficients of determination greater than 0.90. The Ni at the diagnosis leaf ranged between 0.093 (T10) - 0.611 mg.kg-1 (T5). No amounts of Ni were detected on whole plant and grain. The maize grain yield on the area that received sewage sludge for 15 years, ranged around 14.86 to 19.26 t.ha-1, corrected to 13% of moisture and did not differ ...

A produção de resíduos sólidos urbano vem crescendo em virtude do constante aumento populacional. Um destes resíduos é o lodo de esgoto (LE). Este tem se mostrado uma boa alternativa para a fertilização de solos agricultáveis, visto que é um material rico em nutrientes às plantas e fonte potencial de matéria orgânica, por apresentar metais em sua constituição, organismos patogênicos e compostos orgânicos tóxicos. O LE deve ser manejado de maneira cautelosa, visando o uso ambientalmente sustentável. O objetivo deste trabalho foi quantificar o elemento traço níquel no teor pseudototal, disponível, nas frações da matéria orgânica (ácido húmico-AH e ácido fúlvico-AF). Adicionalmente a adsorção deste elemento no solo e também avaliou-se a absorção de níquel por plantas de milho. O experimento foi instalado em condições de campo na área experimental da FCAV/UNESP, Campus de Jaboticabal-SP, em delineamento experimental em blocos casualizados, com 4 tratamentos e 5 repetições. Os tratamentos foram de T0 – sem lodo, T5 – 5 t ha-1 de LE, T10 – 10 t ha-1 de LE e T20 – 20 t ha-1 de LE. O lodo utilizado foi da estação de tratamento ETE-SABESP localizada em Monte Alto-SP. Na camada de 0,05 – 0,10 m de profundidade, o teor de Ni pseudototal aumentou de 75,9 a 107,3 mg kg-1 em função das doses de lodo, embora o teor de Ni disponível não tenha sido alterado. Nas frações da matéria orgânica a camada superficial foi a que mostrou os maiores teores de Ni, tanto para AH quanto para AF, sendo significativo apenas na camada de 0,05 – 0,10 m. Os resultados da adsorção realizada melhor se ajustaram à isoterma de Freundlich com coeficientes de determinação maiores que 0,90. O Ni na folha diagnose variou de 0,093 (T10) – 0,611 mg kg-1 (T5), o níquel em planta inteira e grão não foram detectados, sendo inferior ao limite de detecção para este elemento ...
Keywords: Milho - Adubos e fertilizantes; Solos - Teor de metal pesado; Metais pesados; Niquel; Matéria orgânica; Lodo de esgoto; Heavy metals